Dissolving microneedles for transdermal delivery of huperzine A for the treatment of Alzheimer's disease - Yan, Qinying (Drug Deliv, 2020)
Increasingly attention has been paid to the transdermal drug delivery systems with microneedles owing to their excellent compliance, high efficiency, and controllable drug release, therefore, become promising alternative with tremendous advantages for delivering specific drugs such as huperzine A (Hup A) for treatment of Alzheimer’s disease (AD) yet with low oral bioavailability. The purpose of the present study is to design, prepare, and evaluate a dissolving microneedle patch (DMNP) as a transdermal delivery system for the Hup A, investigating its in vitro drug release profiles and in vivo pharmacokinetics as well as pharmacodynamics treating of AD. Skin penetration experiments and intradermal dissolution tests showed that the blank DMNP could successfully penetrate the skin with an adequate depth and could be quickly dissolved within 5 min. In vitro transdermal release tests exhibited that more than 80% of the Hup A was accumulatively permeated from DMNP through the skin within three days, indicating a sustained release profile. In vivo pharmacokinetic analysis demonstrated that the DMNP group resulted in longer T(max) (twofold), longer t(1/2) (fivefold), lower C(max) (3:4), and larger AUC((0–∞)) (twofold), compared with the oral group at the same dose of Hup A. Pharmacodynamic research showed a significant improvement in cognitive function in AD rats treated with DMNP-Hup A and Oral-Hup A, as compared to the model group without treatment. Those results demonstrated that this predesigned DMNP is a promising alternative to deliver Hup A transdermally for the treatment of AD.